Estudio de factibilidad para la implementación de una fábrica de embutidos en la Ciudad de Esmeraldas - Zambrano Macías, Hernán Oswaldo (2011)
The present project considers the study of feasibility for the development of the project of implementation of a factory of sausages, with the offer to be implemented in the province of Esmeraldas at the noroccidente of the country. During the study a market analysis was realized for different types of niches of market so much for the channel of coverage in shops and small supermarkets as for the marketing towards the final client, it was possible to observe that into the province the principal comercializador of this type of products there is stuffed Don Diego followed by Pronaca's great participation, Nevertheless inside the preferences of the consumer there exists the advantage of which in his habits of consumption also there exists great participation of sausages of slightly recognized brands implying that the fact for choices for that the consumer looks is not the support of the brand of the sausage but his flavor and economy, for it I conclude to the development and implementation of the Project with the production and marketing sausage, jamonada and mortadella…